A network pharmacology approach to elucidate the anti-inflammatory and antioxidant effects of bitter leaf (Vernonia amygdalina Del.) - Sailah, Illah; Tallei, Trina E.; Safitri, Linda; Tamala, Yulianida; Halimatushadyah, Ernie; Ekatanti, Dewi; Maulydia, Nur B.; Celik, Ismail (Narra Sains Indonesia, 2024)
The therapeutic potential of bitter leaf (Vernonia amygdalina Del.) has been established both empirically and in various scientific investigations. However, the molecular pathways related to its possible anti-inflammatory and antioxidant properties remain unclear. Therefore, the aim of this study was to elucidate the molecular interactions between bitter leaf's bioactive compounds and cellular targets involved in these activities. The compounds in bitter leaf were identified using gas chromatography-mass spectrometry (GC-MS) analysis, and subsequently, a network pharmacology approach was employed together with molecular docking and dynamics simulations. Acetonitrile (4.5%) and dimethylamine (4.972%) were the most prevalent compounds among the 38 identified by the GC-MS analysis of bitter leaf extract. The proto-oncogene tyrosine-protein kinase (SRC) demonstrated significant connectivity within the antioxidant network, highlighting its pivotal role in facilitating inter-protein communication. It also exhibited strategic positioning in anti-inflammatory mechanisms based on closeness centrality (0.385). The enrichment analysis suggested multifaceted mechanisms of bitter leaf compounds, including transcriptional regulation and diverse cellular targeting, indicating broad antioxidant and anti-inflammatory effects. Eicosapentaenoyl ethanolamide (EPEA) displayed strong interactions with multiple proteins, including SRC (-7.17 kcal/mol) and CYP3A4 (-6.88 kcal/mol). Moreover, EPEA demonstrated to form a stable interaction with SRC during a 100 ns simulation. In conclusion, the computational simulations revealed that the hypothetical antioxidant and anti-inflammatory actions of bitter leaf compounds were achieved by specifically targeting SRC. However, confirmation using either in vitro or in vivo techniques is necessary.